Hemoglobin F or: How I Learned to Stop Wondering and Love the Flow Cytometer. (11th September 2019) - Fecher, Roger; Choudhuri, Jui; Barouqa, Mohammad; Tolu, Seda; Minniti, Caterina; Gil, Morayma Reyes
Abstract: Sickle cell disease (SCD) is the most common inherited blood disorder in the United States. It is a hemoglobinopathy that leads to red blood cell (RBC) sickling and a broad range of disease complications including vaso-occlusive crisis, acute chest syndrome, and retinopathy. Hydroxyurea, a drug used to treat SCD, is known to increase expression of hemoglobin F (HbF), a type of hemoglobin normally expressed in infancy; HbF levels between 10% and 20% are associated with decreased vaso-occlusive episodes and improved survival. Hereditary persistent hemoglobin F (HPHF), a typically asymptomatic hemoglobinopathy associated with sustained hemoglobin F (HbF) expression into adulthood (HbF >10%), in combination with SCD is associated with decreased complications. Laboratories typically determine the HbF level via high-performance liquid chromatography (HPLC). HbF levels approaching 30% on HPLC are thought to be protective against SCD complications. However, HbF may be found within a majority or minority of RBCs, pancellular (deletional HPHF) or heterocellular distribution (nondeletional HPHF), respectively. Additionally, the quantity of HbF within cells can range from low (<10 picograms/cell) to high (>35 picograms). We sought to determine the quantity and distribution of HbF required to protect against sickle cell disease symptoms both via traditional HPLC as well as flow cytometry. This retrospective study was conducted at a large academic medical center over a period of 2 months (January-February 2019). We collected blood from sickle cell patients that had a detectable HbF level on hemoglobin electrophoresis. We then stained RBCs from 16 of the patients for HbF and performed flow cytometry to examine the HbF distribution. We calculated the cellular concentration of HbF within each HbF+ cell using the formula (MHC × %HbF)/%F-cells. We performed a chart review to determine the native hemoglobin type, exposure to hydroxyurea, and clinical symptoms of sickle cell disease. We identified four patients over the age of 20 with HbS/HPHP and no exposure to hydroxyurea. Two of these patients experienced no sickle cell disease complications; the protected patients had heterocellular distribution of HbF, but had a high concentration of HbF per HbF+ cell (>35 picograms/cell). Notably, these asymptomatic patients both had HbF level by HPLC less than 30. One of the symptomatic HbS/HPHF patients had heterocellular expression of HbF with low cellular concentration (28 picograms/cell) while the other patient had pancellular HbF expression with very low cellular concentration (6.4 picograms/cell). Our study demonstrates that HPHF alone does not prevent sickle cell disease complications. Our study highlights the importance of quantifying the cellular concentration of HbF, which can provide useful information beyond that of HPLC. In addition, our study raises the potential of the clinical use of hydroxyurea in patients with sickle cell disease even in the presence of HPHF.